Report. Issue 2 (1st October 2015) - Villaverde, Elisa Costa
Voicing the voiceless on radio: Language as the only tool – migrations, cultures and identities with audio and no visuals in the digital screen eraA review of the Spanish radio programme A Vivir, que son dos días, directed and presented by Javier del Pino